Within the teacher evaluation policies black box: two case studies. Issue 3 (27th May 2017) - Vaillant, Denise; Gonzalez-Vaillant, Gabriela
Abstract : This paper analyzes the relationship between teacher evaluation policies in Chile and Uruguay, teacher professional development, and teacher performance effectiveness. The analysis tries to understand the extent to which the existing processes for teacher evaluation stimulate an improvement in the quality of teaching. The comparison of two national cases with similar educational results but radically different educational policies allows the authors to take a close look within the 'black box' of educational policy-making. The paper is based on in-depth analysis of the PISA survey to heads of schools and in-depth interviews with teachers, heads, and key informants. The paper finds that policies aiming to strengthen teacher development and teacher performance through teacher evaluation cannot be understood in dichotomist ways; lack of attention to teachers' perspectives and unintended effects of policy implementation can lead to marginal effects. Uruguay, where teacher evaluation policies have weak practical effects, has managed to obtain similar educational results to Chile. However, the experience of Chile shows that teacher evaluation can have an effect on teacher professional development and, in the long run, this may have an effect on the quality of teaching and student results.